Ultrasonographic approach to diagnosing coarctation of the aorta: case report - Salum-Rodríguez, Lucy; Zalapa-Gómez, Maria Fernanda; Moreno-Plata, Héctor Alexandro; Alfredo Rangel-Nava, Hugo (International Journal of Research in Medical Sciences, 2025)
Coarctation is the narrowing of the isthmus or aortic arch. It accounts for approximately 8% of all congenital heart defects; it is a cause of morbidity and mortality if not diagnosed early. Although it is a common congenital cardiac defect, it remains one of the most challenging cardiac defects to diagnose prenatally. Which is why the objective of this case report is to present a prenatal diagnosis of coarctation of the aorta and show how prenatal diagnosis with proper counseling can optimize management, and that learning about the ultrasonographic characteristics that raises suspicion of coarctation of the aorta and referring the patient to a maternal fetal medicine-specialist is a fundamental key to the diagnosis.